JAEPL, Vol. 24, 2018-2019 - Wendy Ryden; Peter H. Khost (Journal of the Assembly for Expanded Perspectives on Learning, 2019)
ESSAYS “Be a Liberation Whatever”: Social Justice Literacy in a Living-Learning Community, Faith Kurtyka Racial Literacy Is Literacy: Locating Racial Literacy in the College Composition Classroom, Mara Lee Grayson SPECIAL SECTION: ENCOUNTERING THE NATURAL WORLD: ENVIRONMENTAL EDUCATION IN THE ARTS AND HUMANITIES Swamps, Flat Earthers, and Boughs of Holly: “Encountering” the Natural World and the Poetics of Environmental Literacy, Wendy Ryden Containing the Jeremiad: Understanding Paradigms of Anxiety in Global Climate Change Experience, Brian Glaser Seeking a Language that Heals: Teaching and Writing from a Ruined Landscape, Amy Nolan Teaching Animals in the Post-Anthropocene: Zoopedagogy as a Challenge to Logocentrism, Anastassiya Andrianova Writing about Wolves: Using Ecocomposition Pedagogy to Teach Social Justice in a Theme-Based Composition Course, Michael S. Geary Relational Literacy, W. Kurt Stavenhagen BOOK REVIEWS Present and Feeling, Irene Papoulis Newkirk, Thomas. Embarrassment and the Emotional Underlife of Learning. Heinemann, 2017, Dan Mrozowski Young, Shinzen. The Science of Enlightenment: How Meditation Works. Sounds True, 2016, Jacquelyne Kibler Peary, Alexandria. Prolific Moment: Theory and Practice of Mindfulness for Writing. Routledge, 2018, Christy I. Wenger De Luca, Geraldine. Teaching toward Freedom: Supporting Voices and Silence in the English Classroom. Routledge, 2018, Mary Leonard Cooper, Brittney. Eloquent Rage, A Black Feminist Discovers Her Superpower, St. Martins, 2018, Sharon Marshall CONNECTING Finding Meaning in our Work and Writing, Christy I. Wenger Response from Beyond, Monica Mische Reflecting on Arguing and Listening in Digital Spaces, Kristina Fennelly Sunday Morning Before Midterms, Laurence Musgrove Honoring Impulse, Attending to Gesture, Lindsey All-good